A Spatio-Temporal Assessment of Green Turtle Habitat at Hawkes Bay, Karachi through Geo-Informatics Techniques - Farheen Khanum,; Syed Jamil H. Kazmi,; Saima Shaikh, (Journal of Basic & Applied Sciences, 2014)
Hawkes Bay site is one of the major favorable nesting sites for green turtles (Chelonia mydas) in Pakistan. Many environmental factors influence the nesting patterns of green turtles at this beach. The main objective of this study is to evaluate the importance of monitoring habitat of wildlife with the help of GIS and remote sensing. Seasonal influence on nesting pit density is quite noticeable on high resolution imageries. Pearson’s correlation coefficient analysis was used to highlight the strong relation of temperature and nesting pits. As a result of this research monitoring of spatio-temporal variation and impacts of temperature rise on nesting grounds observed.